MORFOLOGI FETUS MENCIT (MUS MUSCULUS L.) SETELAH PEMBERIAN EKSTRAK DAUN SAMBILOTO (ANDROGRAPHIS PANICULATA NEES) - SETYAWATI, IRIANI (Jurnal Biologi Udayana; Vol 13 No 2 (2009): JURNAL BIOLOGI, 2009)
This experiment was performed to examine the effects of Andrographis paniculata Nees leaves extract on foetus morphology if given during organogenesis period. Thirty pregnant mice were randomly divided into 5 groups for teratogenic effects. Extract was given orally by gavage with 0 (as control); 0,004 (equal to one time dose to human); 7,5; 15; and 22,5 g/g body weight/ day. Treatment was given from day 6 to day 13 of gestation (organogenesis period). Foetus were removed on day 18 of gestation by caesarean section. Quantitative data were analyzed with Anova and Duncan's Multiple Range Test. The results showed that teratogenic effects increased in dose-related manner by causing foetus death and resorption, hemorrhage and clubfoot.
Keywords: Andrographis paniculata Nees, foetus morphology